The Use of DNA Barcoding and Phylogenetic Analysis to Improve Identification of Usnea spp. Based on ITS rDNA - Miftahul Jannah; Muhammad Rifqi Hariri; Rina Sri Kasiamdari; Niken Satuti Nur Handayani (Journal of Tropical Biodiversity and Biotechnology, 2021)
Lichen of the genus Usnea is quite common being used as a traditional herbal remedy. This genus is characterized by thallus, which is very similar among the species, leads to some difficulties in distinguishing them. In Indonesia, such research report on the availability of this genus based on their morphological characteristic is minimal. This might be due to too high morphological similarities among them. The molecular character, which is based on the DNA Barcode of Internal Transcribed Spacer (ITS) rDNA sequences, with its conserved region (5.8S) and varied region (ITS1 and ITS2), are becoming essential characters on identifying as well as analyzing the phylogenetic. The current study then proposed to identify and draw the species dendrogram of species within the Usnea genus obtained from Mount Lawu Forest of Central Java and Turgo Forest of Yogyakarta based on their phylogenetic and phenetic analysis. The dendrogram was constructed with UPGMA using the simple matching coefficient, whereas the phylogenetic tree was constructed with Maximum Likelihood (ML) using Kimura-2 parameter with 1000 bootstrap. The data were unable to draw phenetic relationships among the subgenus Usnea and Eumitria members. The phylogenetic tree shows the primary two clades, distinguishing the subgenus Usnea and Eumitria. The ITS rDNA sequence was able to identify most of the Usnea species.